(3GdeYLe GdUZjQs - (3SdjeGf Hf CMeO Hf CjhH Hf eWjQ GddNej GdTGej, CHh GdbGSe, J (B360 (3g` s
(3ChdgG (B:s
(3MOKfG CMeO Hf EHQGgje Cf YjGV Hf MeGO GdeLGTYi Ke GdfgTdi CgOi dQShd Gddg Udi Gddg Ydjg hSde aQSkG bHd Cf jSde abGd Efi CcQg OHO GdeTQcjf s
(3BNQgG (B:s
(3SeYJ UdjMI HfJ CHj fYje GdaVd Hf Ocjf Jbhd (B: (3CHj jbhd GdbQBf cdGe Gddg ZjQ eNdhb BNQ GdeYLe GdUZjQ Yf GdWHQGfi hGdMeO ddg hMOg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI Yf CUd ehKb Ydjg SeGYGJ ef GdbQf GdSGOS s
(3YdjgG NW GdMGaX YHO GdeDef Hf Nda GdOejGWi SfI (B701 (3HUMI SeGY GdfSNI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B121s
Keywords: (3GddZIs